International perspectives on physician knowledge, attitudes, and practices related to medical cannabis - Syed, Shariful A.; Singh, Jatinder; Elkholy, Hussien; Rojnić Palavra, Irena; Tomicevic, Marko; Eric, Anamarija Petek; Pinto da Costa, Mariana; Guloksuz, Sinan; Radhakrishnan, Rajiv (Frontiers in Public Health, 2025)
BackgroundThe trends of recreational use of cannabis and the use of cannabis for medical indications (i.e., “medical cannabis”) have grown in recent years. Despite that, there is still limited scientific evidence to guide clinical decision-making, and the strength of evidence for the medical use of cannabis is currently considered to be low. In contrast, there is growing evidence of negative health outcomes related to the use of cannabis. In this rapidly shifting landscape, the role of physician attitudes regarding the therapeutic value of cannabis has become essential. This study aimed to characterize knowledge/experience, attitudes, and potential predictors of clinical practice regarding medical cannabis.MethodsWe conducted a cross-sectional survey of physicians from 17 countries between 2016 and 2018. The survey consisted of questions designed to explore physician knowledge, attitude, and practices regarding the use of medical cannabis. Descriptive statistics were used to examine willingness to recommend medical cannabis for medical and psychiatric indications, followed by regression analysis to identify the predictors of physician willingness to recommend medical cannabis.ResultsA total of 323 physicians responded to the survey, among which 53% were women. The mean age was 35.4 ± 9.5 years, with 10.04 ± 8.6 years of clinical experience. Clinical experience with medical cannabis was overall limited (51.4% noted never having recommended medical cannabis and 33% noted inadequate knowledge regarding medical cannabis). The majority of respondents (84%) recognized the risk of psychosis with cannabis use, while only 23% correctly identified the risk of addiction with daily cannabis use. Overall, willingness to recommend medical cannabis was the highest for chemotherapy-induced nausea (67%), refractory chronic neuropathic pain (52%), and spasticity in amyotrophic lateral sclerosis (ALS; 51%).ConclusionThis international study examining physician knowledge, attitudes, and practices related to medical cannabis revealed that there are significant gaps in domain-specific knowledge related to medical cannabis. There is a wide variability in willingness to recommend medical cannabis, which is not consistent with the current strength of evidence. This study thus highlights the need for greater education related to domain-specific knowledge about medical cannabis.